2015
DOI: 10.1186/s12966-015-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity and sedentary time in youth: the International children’s accelerometry database (ICAD)

Abstract: BackgroundPhysical activity and sedentary behaviour in youth have been reported to vary by sex, age, weight status and country. However, supporting data are often self-reported and/or do not encompass a wide range of ages or geographical locations. This study aimed to describe objectively-measured physical activity and sedentary time patterns in youth.MethodsThe International Children’s Accelerometry Database (ICAD) consists of ActiGraph accelerometer data from 20 studies in ten countries, processed using comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

90
640
19
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(773 citation statements)
references
References 35 publications
90
640
19
24
Order By: Relevance
“…This is supported by accelerometer data from over 27,000 children and adolescents (aged 3 to 18) from 20 studies in ten countries which showed that only 9% of the boys and 2% of the girls met the WHO recommendations (Cooper et al, 2015).…”
Section: Introductionmentioning
confidence: 71%
“…This is supported by accelerometer data from over 27,000 children and adolescents (aged 3 to 18) from 20 studies in ten countries which showed that only 9% of the boys and 2% of the girls met the WHO recommendations (Cooper et al, 2015).…”
Section: Introductionmentioning
confidence: 71%
“…In the recent study of Cooper et al [5], it was found that in all 20 studied countries only 9% boys and 1.9% 5-17-year-old girls met the guidelines of achieving 60 min of MVPA every day. Daily physical activity tends to decrease during puberty [6].…”
Section: Introductionmentioning
confidence: 88%
“…Sin embargo, un estudio longitudinal desde los 13 hasta los 23 años evidenció que los niveles de AF sufren un descenso progresivo en la transición entre la adolescencia y la etapa joven adulta (Kjønniksen, Torsheim, & Wold, 2008). En esta misma línea, una reciente revisión sistemática llevada a cabo por Cooper et al (2015) en 27.637 niños y adolescentes (2-18 años) de 10 países señalaron que a partir de los cinco años se producía un descenso medio del 4.2% sobre los niveles de AF. En el contexto español, el abandono de la práctica físico-deportiva parece también más acusado en la etapa de la adolescencia, concretamente en el periodo de Bachillerato (Macarro, Romero, & Torres, 2010), que se establece como un punto transitorio a la entrada en la formación profesional de grado superior u otras enseñanzas superiores o en la enseñanza universitaria.…”
Section: Introductionunclassified
“…Para ello, existen numerosas variables que pueden ayudar a explicar el comportamiento de práctica de AF. Dentro de los factores socio-demográficos que influyen en la práctica de AF existen numerosas evidencias que señalan que los chicos son más activos que las chicas en todos los rangos de edad en la adolescencia (Cooper et al, 2015). En esta misma línea, los chicos realizan más práctica deportiva extraescolar que las chicas (Isorna, Rial, & Vaquero-Cristóbal, 2014).…”
Section: Introductionunclassified